Handbook of gender and mobilities - Preston, Valerie; McLafferty, Sara L.; Maciejewska, Monika; Yeoh, Brenda S. A. (Edward Elgar Publishing, 2024)
"This important Handbook provides a critical overview of the complex links between gender, mobility, and immobility, emphasizing the production and politics of gendered mobilities and the importance of gender perspectives. Expert contributors investigate key issues such as mobility transitions across the life course; the links between gender, caregiving and everyday mobilities; and the gendered opportunities and constraints for international migrants. The studies critically examine the gendered impacts of transportation infrastructure and sustainability policies such as 15-minute cities and free-fare public transport. Drawing on empirical research from across the globe, the Handbook of Gender and Mobilities highlights how class, ethnicity and race, ableism and age shape gendered mobilities across different spatial scales. This Handbook is an excellent read for students and researchers looking for an up-to-date resource for mobility studies, urban studies, feminist geography, transportation geography, urban geography, and migration studies. The cogent and succinct summaries of current research will be especially informative and useful for policy makers and transportation planners"--
Includes bibliographical references and index